Experimental and Numerical Simulation Study on the Antipenetration Properties of Fiber Ceramic-Reactive Powder Concrete Composite Targets - H. H. Zou; C. M. Song; M. Y. Wang; D. R. Wang; D. S. Wen (Shock and Vibration)
Composite materials have been demonstrated to possess excellent antipenetration capacities, but the existing studies have not involved the penetration characteristics of ceramic-concrete composite targets. To investigate the antipenetration mechanisms of fiber ceramic-reactive powder concrete (FC-RPC) composite targets, three pieces of FC-RPC composite targets were designed to perform penetration tests. Antipenetration tests were performed with a special howitzer with a diameter of 125 mm. The test parameters, such as the impact velocity, failure pattern of projectiles, penetration depth, crater diameter, and failure model of targets, were obtained. It was found that the FC-RPC targets exhibited an excellent antipenetration capacity and failed in a ductile manner, the target caused an obvious erosion effect on projectiles at low speed (i.e., 375 m/s), and the antipenetration performance of the composite target was improved by increasing the thickness of the FC target. Simultaneously, numerical simulations of FC-RPC targets subjected to projectile impact were carried out by using LS-DYNA codes. Separately, combined and integrated finite element models were used to analyze the effect of the fiber layer in the composite target. The numerical results of the combined model were in good agreement with the experimental data, and the reliabilities of simulation were validated. The differential protection factor of the FC-RPC targets was obtained based on the penetration tests and numerical simulation, and an empirical formula for multilayer targets was presented.